1994
DOI: 10.1002/jso.2930550310
|View full text |Cite
|
Sign up to set email alerts
|

Lymphokine‐activated killer cell activity of peripheral blood, spleen, regional lymph node, and tumor infiltrating lymphocytes in gastric cancer patients

Abstract: Lymphokine-activated killer (LAK) cell activity of peripheral blood mononuclear cells (PBM), spleen cells (SPC), regional lymph node cells (LNC), and tumor-infiltrating lymphocytes (TIL), induced by activation with interleukin 2 (IL 2) for 4 days, was evaluated in patients with gastric carcinoma. TIL exhibited the lowest LAK activity and the cytotoxicity of LNC was significantly lower than that of either PBM or SPC. There was no difference between PBM and SPC. Then, there were significant correlations of LAK a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Okada et al (1995) found abundant CD57+ TIC in CRC patients, the majority of which being CD4−, half CD8 +, and one third γδ TCR+. Other investigators have reported that CD57+ cells were one of the major TIL, especially in patients with gastric carcinoma (Karimine et al , 1994; Arinaga et al , 1995). However, they did not examine whether or not such CD57+ cells express CD3 (or TCR).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Okada et al (1995) found abundant CD57+ TIC in CRC patients, the majority of which being CD4−, half CD8 +, and one third γδ TCR+. Other investigators have reported that CD57+ cells were one of the major TIL, especially in patients with gastric carcinoma (Karimine et al , 1994; Arinaga et al , 1995). However, they did not examine whether or not such CD57+ cells express CD3 (or TCR).…”
Section: Discussionmentioning
confidence: 94%
“…However, they did not examine whether or not such CD57+ cells express CD3 (or TCR). In other words, they considered these cells as NK cells rather than CD3+ T cells (Karimine et al , 1994; Arinaga et al , 1995). More recently, CD8+ and CD57+ T cells with cytotoxic functions were found in patients with multiple myeloma (Sze et al , 2001).…”
Section: Discussionmentioning
confidence: 99%
“…15,16 CD57 + T cells have been shown to mediate immunoregulatory functions rather than CTL effector functions. CD56 + T cells and CD57 + T cells are increased in the peripheral blood and/or among tumor infi ltrating lymphocytes (TIL) in patients with gastric [17][18][19] and colorectal T cells), and NK-like T cells (CD56 + T cells and CD57 + T cells) in the peripheral blood of 48 gastric cancer patients and 20 healthy controls were measured by two-color fl ow cytometry analysis and by intracellular cytokine analysis to investigate an association of these immune cells with the survival rate of gastric cancer patients. Results.…”
Section: Introductionmentioning
confidence: 99%
“…Several Investigators have reported that CD57 ^ cells were one of the major infiltrating lymphocytes into the tumour sites, especially in patients with gastric carcinoma [22][23][24]. However.…”
Section: Discussionmentioning
confidence: 99%